WORK FAMILY CONFLICT PADA IBU BEKERJA PENDAMPING PEMBELAJARAN DARING - Alya Ulfah Az-Z (2022)
This research is based by the role overload that occurs in working mothers during the Covid-19 pandemic, they have to carry out their roles as workers and fulfill their roles as housewives, during the pandemic, working mothers also have to take a role as teachers to help and guide children in daring learning. The purpose of this study is to provide an overview of work family conflict during the pandemic such as the background of working mothers, conflicts that occur in working mothers and the efforts made to minimize conflict. This research examines four working mothers with primary school children from socioeconomic backgrounds. According to data analysis, it can be said that during the pandemic, mother identified conflict that was time based conflict, strain based conflict dan behaviour based conflict. Conflicts can caused by work related factor, family related factors and idividual related factors. Working mother can reduce the conflict by engaging in activities such as going for walks, sharing and watch favorite TV programs.